Screening of New Born Babies for Thyroid Stimulating Hormone, Glucose-6-Phosphate Dehydrogenase, 17-Hydroxyprogesterone and Sickle Cell Disease - Kalouni, Mukunda Raj; Badade, Z G; Mohanty, Nimain; Bhatta, Bhup Dev; Pandey, Bhupendra R; Bhatt, Rajendra Dev (Annals of Clinical Chemistry and Laboratory Medicine, 2015)
BACKGROUND: The expanded newborn screening programme has now initiated worldwide. Many of the countries around the world made this programme mandatory. The effect of such screening system gives the advantage or betterment to the society as well as the nation.METHODS: Samples were collected from babies aged 48-72 hours by heel prick method in a filter paper provided by Bio-Rad. The written consent was taken from the parents before collecting the blood samples. Blood samples were assayed for TSH and17-OHP by Enzyme Immuno Assay (EIA), G-6-PD was estimated by colorimetric assay provided by Bio-Rad Laboratories, USA and Sickle Cell Disease by sickling testRESULTS: A total of 715 newborns were screened for TSH, G-6-PD, 17-OHP and Sickle cell disease. Out of which 1 neonate found abnormal (increased) thyroid stimulating hormone (1/715), and 8 neonates were G-6-PD deficient (8/715). We did not find any cases of congenital adrenal hyperplasia and sickle cell disease.CONCLUSIONS: In this study the prevalence of Congenital Hypothyroidism and Glucose-6-Phosphate dehydrogenase deficiency was found to be 1:715 and 1:89 respectively. No cases of congenital adrenal hyperplasia and sickle cell disease were found.